Bridging Divides : Enabling Urban Capabilities - Sassen, Saskia (World Bank, Washington DC, 2014)
Cities benefit from two key conditions, both with direct implications for social, cultural, and economic integration. One is a large middle class and a large sector of modest profit-making firms, distinct from a sharp concentration of incomes and profits. The other is a well-distributed urban economy: robust neighborhood sub economies preventing excessive economic concentration in the center, and good transportation for people and goods- not only to the center but also transversally. The urban economy is marked by capture at the top, poorer middle classes, larger destitute populations, and more crime and conflict. These challenges, though present in cities the world over, play out differently in smaller, prosperous cities in Europe and North America than in megacities in Asia, Africa, and Latin America. But cities today are also seeing a massive upgrading of infrastructure in city centers and high value neighborhoods. One outcome is widespread homelessness and destitution, even in cities where these problems had become rare by the mid- to late 20th century. The reasons for this juxtaposition vary enormously due to the differences among cities and among the national economies and societies in which they function. Some cities are sinking under the weight of the negatives, while others are, more recently, succeeding. The major challenges that confront cities and society in general have increasingly strong feedback loops that disassemble the old civic urban order. Fighting climate change may well force citizens and immigrants to work together, regardless of religion, culture, or phenotype.